Role of intermolecular interaction between hydrophobic blocks in block-selected inclusion complexation of amphiphilic poly(ethylene oxide)-poly[(R)-3-hydroxybutyrate]-poly(ethylene oxide) triblock copolymers with cyclodextrins - Li, X. (2014)
10.1016/j.polymer.2004.07.038